An adaptive control system for the optimization of the interactive user response - Perera, Bodiyabaduge Rohan Joseph; Vilas Wuwongse; Malik, Ghulam M.; Huynh, Ngoc Phien; Government of Australia (Bangkok : Asian Institute of Technology, 1983)
The study covers the analysis, design and evaluation of an adaptive control system for a computer installation. The control system optimizes an aggregate objective function, through the dynamic control of a chosen scheduling parameter. The initial investigation includes a study of individual and collective user behavior. The individual behavior determines the controllable objectives of the computer system, and the scheduling options available. Collective behavior determines the system performance under the proposed scheduling method. The control system extends the concepts of equality of service and of processor sharing to include the total cumulative CPU usage of individual customers. This is achieved by modifying the simple multi-class feedback scheduling algorithm to take into account the previous CPU usage . Users are assigned priorities according to their previous CPU usage. A closed form analytical expression for the waiting time of interactive users is developed using a simplified model of the computer system. The load variation is monitored and is used to adjust the parameters of the model. Using the updated model the scheduling parameter is dynamically adjusted to provide the optimal operating value. The control system is designed a s a collection of independent subsystems, interaction being achieved through the use of common data and parameter files. The basic assumptions are tested using a GPSS simulation model of the system.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1983
Keywords: Adaptive control systems -- Mathematical models